Gauging the efficiency of bank consolidation during a merger wave - Calomiris, Charles W. (Journal of Banking & Finance, 1999)
By many measures, bank consolidation waves, historically and currently, produce substantial efficiency gains associated with reduced operating costs, enhanced diversification, and the enrichment of bank-customer relationships. These gains may be hard to discover in panel or cross-sectional analyses of individual banks because merger waves pose special econometric pitfalls for event studies of stock returns and bank performance comparisons. We review these problems and summarize lessons from nine case studies of individual merger transactions which offer qualitative evidence that potential econometric pitfalls can be important. Those conclusions suggest placing greater weight on cross-regime comparisons for measuring gains during bank merger waves.